Subjective assessment of mastication as parameter for successful prosthetic therapy - Milekić Bojana; Puškar Tatjana; Marković Dubravka (Serbian Medical Society - Dental Section, Belgrade, 2009)
Introduction. Success in functional rehabilitation of the craniomandibular system in patients without teeth, which have total prosthesis, can be assessed using different clinical and functional methods. Subjective assessment, motivation, comfort level and functional efficacy are important elements for adaptation to dental prosthesis as well as base for success in prosthetic therapy. The aim of this study was to evaluate the importance of subjective assessment of the mastication in people with new dental prosthesis as well as to assess the value of that parameter in determining the successful prosthetic therapy. Material and Methods. Study was conducted at the Dental Clinic in Novi Sad. Thirty patients (16 males and 14 females) with average age of 62.5 years who received total prosthesis were included. Analysis was done according to the data from the medical records and conducted survey in the form of questionnaire which was adjusted to our clinical examinations. Results. Results showed that 96.6% of the patients were satisfied with new prosthesis. Subjective assessment of the quality of their mastication before therapy showed that 63.4% consider their mastication as unsatisfied, 26.6% satisfied while 10% of toothless patients thought their mastication was good. Statistic analysis showed there was significant difference in subjective assessment before and after the therapy (p<0.01). In fact, there was significant connection between subjective assessment of the mastication and satisfaction with new prosthesis and therapy at all (p<0.01). Conclusion. Patients satisfaction with total prosthesis and subjective assessment of mastication are in direct correlation with successful prosthetic treatment. Results of subjective assessment of the mastication are important and can be used as a parameter for success along with precise survey.